Knowledge, attitudes and awareness of Cardiopulmonary Resuscitation in physiotherapists of Karachi–A Cross-sectional Survey - Sobia Hasan, Muhammad Fareed Nasir, Khurrum Amin, Sadia Sundus, Shazia Dawood, Sabika Minhaj (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To study and relate the level of knowledge and attitude regarding CPR in medical faculty of Karachi. Research Design: This was an observational, cross-sectional survey based study. Duration: December, 2020 to January, 2021. Methodology: This study was conducted in various private and public sector hospitals and private rehabilitation centers in Karachi. This was an observational, cross-sectional, survey based study designed to assess CPR knowledge. Data was collected using a self–structured questionnaire comprising of thirty one close-ended questionnaire having 3parts: Q.1-7 Demographics; Q.8-20 CPR Practices and Q.21-31 Knowledge of CPR. Result: Total Sample of 126 individuals (n=126) was selected for the study. The analysis was done by using SPSS version 22. The P value (>0.05) indicates that the outcomes were insignificant indicating the knowledge of CPR in Karachi. Conclusion: The general awareness regarding CPR was good but ﬁrst aid skills needs improvement. Professional training programs, hands-on workshops, should be conducted to enhance CPR skills, awareness and knowledge among medical faculty.